2017
DOI: 10.3168/jds.2016-11561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forage provision to dairy calves on growth performance and rumen fermentation: A meta-analysis and meta-regression

Abstract: A meta-analysis of the potential effect of forage provision on growth performance and rumen fermentation of dairy calves was conducted using published data from the literature (1998-2016). Meta-regression was used to evaluate the effects of different forage levels, forage sources, forage offering methods, physical forms of starter, and grain sources on the heterogeneity of the results. We considered 27 studies that reported the effects of forage provision to dairy calves. Estimated effect sizes of forage were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 45 publications
(86 reference statements)
6
61
1
8
Order By: Relevance
“…Similar to previous studies conducted with individually housed calves provided lowquality hay or straw (Khan et al, 2011;Castells et al, 2012;Montoro et al, 2013), we found that providing hay to calves did not affect starter intake and therefore resulted in greater total DMI during the pre-weaning stage, particularly during the week before weaning. Interestingly, however, calves in our study selected forage at a higher inclusion rate (15%) than is often observed or recommended (e.g., <10%; Castells et al, 2012Castells et al, , 2013, and a recent meta-analysis has also suggested that high levels of forage (>10% dietary inclusion) are associated with increased starter intake (Imani et al, 2017), suggesting that further evaluation of optimal dietary inclusion of forage may be needed. Aside from effects of forage type, we speculate that the amount of hay selected may depend on milk feeding level; whereas most research in this area has been conducted with calves provided restricted milk allowances (e.g., 10% of birth weight or 4 to 5 L/d; Coverdale et al, 2004;Castells et al, 2012Castells et al, , 2013, Khan et al (2011) provided milk at the same feeding level as the present study (8 L/d) and reported similar levels of hay intake.…”
Section: Behaviormentioning
confidence: 72%
“…Similar to previous studies conducted with individually housed calves provided lowquality hay or straw (Khan et al, 2011;Castells et al, 2012;Montoro et al, 2013), we found that providing hay to calves did not affect starter intake and therefore resulted in greater total DMI during the pre-weaning stage, particularly during the week before weaning. Interestingly, however, calves in our study selected forage at a higher inclusion rate (15%) than is often observed or recommended (e.g., <10%; Castells et al, 2012Castells et al, , 2013, and a recent meta-analysis has also suggested that high levels of forage (>10% dietary inclusion) are associated with increased starter intake (Imani et al, 2017), suggesting that further evaluation of optimal dietary inclusion of forage may be needed. Aside from effects of forage type, we speculate that the amount of hay selected may depend on milk feeding level; whereas most research in this area has been conducted with calves provided restricted milk allowances (e.g., 10% of birth weight or 4 to 5 L/d; Coverdale et al, 2004;Castells et al, 2012Castells et al, , 2013, Khan et al (2011) provided milk at the same feeding level as the present study (8 L/d) and reported similar levels of hay intake.…”
Section: Behaviormentioning
confidence: 72%
“…Forage inclusion in the pre-weaned calf diet has long been discouraged due to its negative effect on the growth rate [15,17]. However, recent research has shown that several factors need to be taken into account when evaluating the impact of forage provision on calf performance [8,9,34]. These factors include the source, amount, particle size, physical form, offering time, and feeding method of forage and concentrate, as well as the amount of milk offered and milk feeding method.…”
Section: Factors That Affect Calf Performance With Forage Inclusionmentioning
confidence: 99%
“…Although the forage intake during the suckling phase supports the physical development of the rumen (HILL et al, 2008), the altered fermentation profile slows down the growth of ruminal papillae (KHAN et al, 2011). In contrast, recent studies have supported the use of forage for calves during the suckling phase as a strategy to increase the concentrate intake and weight gain, and reduce abnormal calf behavior (CASTELLS et al, 2012;IMANI et al, 2017;TERRÉ et al, 2013), especially in intensive rearing systems. In addition, as the physical form of the forage may influence the development of the rumen (CASTELLS et al, 2012;MONTORO et al, 2013), the availability, digestibility, and percentage of leaves are important factors to be considered for optimizing the development of calves.…”
Section: Resultsmentioning
confidence: 99%